Mass transfer rate effects on the cavitating vortex shedding flow around a circular cylinder at a low Reynolds number. Issue 1 (1st June 2022) - Chen, J; Escaler, X
Abstract: Cavitating vortex shedding is a flow phenomenon commonly encountered behind bluff bodies in hydraulic machinery and systems. The generated vapor bubbles significantly change the dynamic behaviors of the vortices. In addition, the collapses of the cavities become major sources of unwanted effects such as vibration, noise and material erosion. In this study, the numerical results of the cavitating vortex shedding behind a circular cylinder at a low Reynolds number have been compared and analyzed using different mass transfer rate values between the vapor and the liquid water phases. For that, the transport equation for the vapor volume fraction coupled with the source term based on the simplification of the Rayleigh-Plesset equation has been solved. Commonly, this source term that accounts for the mass transfer rate is a function of the pressure difference, the vapor volume fraction, and the empirical factors. To understand the effects of this rate, its has been gradually increased from its default value up to the infinite when the equilibrium assumption is satisfied. The current results show that as the rate increases, higher gradients of the vapor volume fraction and of the pressure near the interface between the vapor and the liquid phases are predicted. As a consequence, the frequency of the vortex shedding is also affected by the variation of the mass transfer rate.